Species richness and vertical stratification of epiphytic lichens in subtropical primary and secondary forests in southwest China. (October 2015) - Li, Su; Liu, Wen-Yao; Li, Da-Wen; Song, Liang; Shi, Xian-Meng; Lu, Hua-Zheng
Abstract: An entire-tree investigation was conducted in two primary and three secondary forest types in the subtropical Ailao Mountains of southwest China to determine whether species richness and vertical stratification of epiphytic lichens responded to forest type and host attributes. Lichen species number, composition and cover differed significantly among forest types and tree species, while tree diameter and tree height had a modest influence. Epiphytic lichen species and functional groups showed clear vertical stratification. Epiphytic lichens were richer in canopies than on trunks and exhibited a great preference for the intermediate zones of trees, while five lichen groups showed distinct vertical diversification. The stratification patterns are clearly related to forest type and may reflect the microclimatic requirements of individual species, e.g. light availability and humidity. Highlights: We analyzed the vertical stratification of epiphytic lichens in subtropical forests. Clear stratification of epiphytic lichen species and functional group were found. The vertical pattern were significantly influenced by forest type and tree attributes. This study offered useful information for forest conservation and management.